Comparing Levels of Positive Mental Well‐Being and Life Satisfaction Between Mothers and Fathers of Children With an Intellectual Disability - Antoniadou, Marina; Totsika, Vaso; Langley, Emma; Hastings, Richard P.; Williams, Caitlin A. (Journal of intellectual disability research, 2025)
Positive mental health is experienced by parents of children with intellectual disability and has been shown to be associated with child mental health outcomes in these families. There is a dearth of evidence on mother-father differences in levels of positive mental health, despite evidence of differences in levels of mental health problems. This study aimed to compare levels of positive mental health, namely life satisfaction and mental well-being, between mothers and fathers of children with an intellectual disability. Participants were 85 mother-father dyads participating in the 1000 Families Study, a UK-based cohort study of families of children with intellectual disability. Approximately 92% of the dyads were a couple, while the rest reported they were divorced, separated or not living with the child's other parent. Over 90% of participants were the child's biological parent. The mean age of mothers and fathers was 45 years old and 50.5 years old, respectively. Children were on average 14.8 years old (ages ranged from 9 to 20 years old) and over 70% were boys. Multilevel models initially showed no differences between mothers' and fathers' mental well-being and life satisfaction. After controlling for other factors potentially related to positive mental health, findings indicated that life satisfaction was reported at higher levels by mothers compared with fathers of children with intellectual disability. Subject to replication in future studies, initial evidence of gender differences in life satisfaction highlights that fathers of children with an intellectual disability may be particularly vulnerable to lower levels of positive mental health. Fathers may require additional support for achieving positive mental health.